A Novel Prehydrated Porcine-Derived Acellular Dermal Matrix: A Histological and Clinical Evaluation - Andreas van Orten; Werner Goetz; Hakan Bilhan (International Journal of Biomaterials)
It is well known that soft tissue quality and quantity around dental implants is of paramount importance for later peri-implant health. For this purpose, the clinical and histological outcomes of the peri-implant mucosa, following soft tissue augmentation for soft tissue improvement with a novel prehydrated porcine acellular dermal matrix graft (PPADMG) in conjunction with simultaneous implant placement, were evaluated in this case series. Twenty-two patients were included in the study. They underwent a late implant placement protocol combined with PPADMG for soft tissue augmentation. A punch biopsy was taken at the time of uncovery of the submerged healed implant after a mean of 157 days healing time. Supracrestal soft tissue height (STH) was measured at the time of implant placement and uncovery. All sites showed a clinical increase in STH. The histological structure of the biopsies resembled a similar structure as found in the healthy oral mucosa. No unexpected tissue reactions could be found. Within the limits of this clinical and histological study, it may be concluded that STH improvement with this novel porcine-derived acellular dermal matrix, in combination with simultaneous implant placement, is a viable option to create a peri-implant tissue thickness and stability.